Six tree species physiological responses to air pollution in Pulogadung Industrial Estate, East Jakarta, Indonesia and Universitas Indonesia Campus, Depok, Indonesia - Ananda Putri; Ratna Yuniati; Afiatry Putrika (Institute of Advanced Engineering and Science, 2023)
Air pollution is a global issue that has a harmful impact on living things and the environment. It is commonly recognized that bioremediation, including the use of tree plants, helps reduce air pollution. Tree plants can respond physically to air pollution. The value of the air pollution tolerance index (APTI) can be used to determine the physiological response. Based on APTI values, this study seeks to determine the tolerance levels and physiological response differences of six tree plant species (Mangifera indica, Pterocarpus indicus, Cerbera odollam, Pometia pinnata, Syzygium myrtifolium, and Swietenia macrophylla) in Pulogadung Industrial Estate, East Jakarta and Universitas Indonesia (UI) Campus, Depok. Environmental factors and APTI values with relative water content parameters, leaf extract pH, ascorbic acid content, and total chlorophyll content were measured in six kinds of tree plants at both research sites. The maximum APTI score in the Pulogadung Industrial Estate was 9.79 0.13, indicating that Mangifera indica plants are air pollution tolerant. Meanwhile, Pterocarpus indicus is classified as sensitive to air pollution, with the lowest APTI score of 6.59 0.18 at the UI Campus, Depok. The APTI test results revealed that tolerant species had high relative water content (RWC) values and ascorbic acid concentration, whereas sensitive species had low RWC values and poor total chlorophyll content.